Estudio de prefactibilidad de una fundación que ofrezca servicios de refuerzos escolares y acompañamiento de tareas a hijos de colaboradores que estén cursando grados de básica primaria de la empresa Universal de Limpieza S.A.S. (2021)
The objective of this project is to carry out a pre-feasibility study for the creation of a foundation that offers school reinforcement services and homework support to the children of collaborators of the Universal de Cleaning S.A.S. who are studying elementary school grades in Bogotá. This study was born from the need to generate a social responsibility project that becomes a solution for UL's business community through care in safe environments and fostering the study of their children, becoming a valuable differential before its collaborators, clients and competitors.